A Study on the Earthquake Generating Faults in Ranau region, Sabah using Satellite Images and Field Investigation - M Batmanathan, Navakanesh (Curtin University, 2018)
This thesis investigates the evidence of active tectonics in Sabah, Malaysia. Our geomorphic data result reveals a number of active normal faults. The field visits also reveal a number of normal faults with NW or SE dipping plane, particularly in Ranau and Kundasang region. Therefore, it is possible that the instrumental and historical seismicity in Sabah is related to these faults, which are formed in response to stresses that are mainly tectonic in origin.